Islamic Education Fungsi Pendidikan Islam Dalam Perspektif Al-Qur’an: Sebuah Literatur-Based Study Atas Q.S Al-Baqarah (2): 151: The Role of Islamic Education from the Qur’anic Perspective: A Literature-Based Study of Surah Al-Baqarah (2): 151 - Luthfia Hanifatus Saiyidah; Muhammad Akmansyah; A. Fathoni; Amirudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Functions of Islamic Education Based on the Perspective of the Qur’an, particularly Surah Al-Baqarah (2):151, emphasize three main educational roles: the recitation of verses, the purification of the soul and the transmission of wisdom contained within the verse. This study employs a literature-based approach by examining classical exegesis, Islamic educational literature, and research published in the last five years. The analysis reveals that the function of Islamic education is not merely oriented toward the transmission of knowledge, but also toward introducing and teaching morals, spiritual awareness, and self-development for students. It can thus be affirmed that Islamic education is essentially integral and transformative, and therefore needs to be implemented in both the written curriculum and in practice, within and beyond the classroom. The implications of this study highlight the crucial role of teachers in education, particularly in guiding students’ spiritual development while simultaneously serving as facilitators of knowledge.